Yacon syrup: Beneficial effects on obesity and insulin resistance in humans - Genta, Susana Beatriz de Fátima (2009)
Background & aims: Syrup obtained from yacon roots could be well positioned as a nutraceutical product due to its high fructooligosaccharides content. We examined the beneficial effects and tolerance of yacon syrup on human health. Methods: Obese and slightly dyslipidemic pre-menopausal women were studied over a 120-day period in a double-blind placebo-controlled experiment. We used two doses of yacon syrup, 0.29 g and 0.14 g fructooligosaccharides/kg/day. At the start and end of the study, anthropometric measurements, blood glucose, calcium, lipid and insulin concentrations and Homeostasis Model Assessment index were determined. Results: The recommended daily consumption of yacon syrup with no undesirable gastrointestinal effects is 0.14 g fructooligosaccharides/kg. Daily intake of yacon syrup produced a significant decrease in body weight, waist circumference and body mass index. Additionally, decrease in fasting serum insulin and Homeostasis Model Assessment index was observed. The consumption of yacon syrup increased defecation frequency and satiety sensation. Fasting glucose and serum lipids were not affected by syrup treatment and the only positive effect was found in serum LDL-cholesterol levels. Conclusions: Yacon syrup is a good source of fructooligosaccharides and its long-term consumption produced beneficial health effects on obese pre-menopausal women with insulin resistance.